Multivessel coronary revascularization and outcomes in kidney transplant recipients - Lenihan, Colin R. (2013)
Coronary artery disease is a major cause of morbidity and mortality in the kidney transplant population. We compared the long-term outcome of coronary artery bypass graft (CABG) surgery with percutaneous coronary artery intervention (PCI) for multivessel coronary disease in a contemporary cohort of US kidney transplant recipients. From the U.S. Renal Data System, we identified all adult kidney transplant patients with ≥ 6 months of Medicare A+B undergoing first recorded multivessel coronary revascularization from 1997–2009. The associations of CABG versus PCI with death and the composite of death or myocardial infarction (MI) were compared using proportional hazards regression. Of the 2272 patients included in the study, 1594 underwent CABG and 678 underwent PCI. The estimated 5-year survival rate was 55% (95% confidence interval [CI] 53% to 57%) following coronary revascularization, with no significant association between revascularization type and death (adjusted hazard ratio [aHR]=1.08;CI 0.94 to 1.23) or the composite of death or MI (aHR = 1.07; CI 0.96 to 1.18). Separate propensity score matched analyses yielded similar results. In this analysis of kidney transplant recipients undergoing multivessel coronary revascularization, we found no difference between CABG and PCI in terms of survival or the composite of death and MI.